Family Health Promotion: Perawatan Luka Pascakhitan, Metode Konvensional yang Optimal di Wilayah Pontianak Selatan - Tutur Kardiatun; Surtikanti Surtikanti; Wien Fitrian R.; Sri Ariyanti; Yuniar Fadila (Abdimas Universal, 2023)
Circumcision has proven health benefits. Circumcision is a type of acute wound that requires wound care that is free from infection and moist wounds. Parents assume that the circumcision wound will heal by itself and no disease or abnormality will occur. The impact of post-circumcision wounds leading to further health problems can be prevented through parental behavior in caring for post-circumcision wounds. Problems arising from post-circumcision such as phimosis (a condition where the foreskin cannot be pulled back from around the tip of the penis), preventing urinary tract infections, making the penis clean, and reducing the risk of developing penile carcinoma. The purpose of this health promotion is to increase parents' knowledge about post-circumcision wound care in order to provide mental readiness for children who will undergo circumcision. The target of this health promotion is the community in Jalan Wonobaru Gang Madyosari, South Pontianak. The method of implementation this health promotion includes discussion and simulation with the stages of preparation, implementation, and evaluation. The results of this health promotion obtained 77% of participants were able to answer the questions correctly and two participants were able to practice the conventional method of post-circumcision wound care. Health promotion participants revealed that knowing post-circumcision wound care is important to minimize complications.